Precise control of liposome size using characteristic time depends on solvent type and membrane properties - Sunghak Choi; Bongsu Kang; Eunhye Yang; Keesung Kim; Moon Kyu Kwak; Pahn-Shick Chang; Ho-Sup Jung (Scientific Reports, 2023)
Abstract Controlling the sizes of liposomes is critical in drug delivery systems because it directly influences their cellular uptake, transportation, and accumulation behavior. Although hydrodynamic focusing has frequently been employed when synthesizing nano-sized liposomes, little is known regarding how flow characteristics determine liposome formation. Here, various sizes of homogeneous liposomes (50–400 nm) were prepared according to flow rate ratios in two solvents, ethanol, and isopropyl alcohol (IPA). Relatively small liposomes formed in ethanol due to its low viscosity and high diffusivity, whereas larger, more poly-dispersed liposomes formed when using IPA as a solvent. This difference was investigated via numerical simulations using the characteristic time factor to predict the liposome size; this approach was also used to examine the flow characteristics inside the microfluidic channel. In case of the liposomes, the membrane rigidity also has a critical role in determining their size. The increased viscosity and packing density of the membrane by addition of cholesterol confirmed by fluorescence anisotropy and polarity lead to increase in liposome size (40–530 nm). However, the interposition of short-chain lipids de-aligned the bilayer membrane, leading to its degradation; this decreased the liposome size. Adding short-chain lipids linearly decreased the liposome size (130–230 nm), but at a shallower gradient than that of cholesterol. This analytical study expands the understanding of microfluidic environment in the liposome synthesis by offering design parameters and their relation to the size of liposomes.